Ferréz: produção material e cultural na quebrada - Sugayama, Soraya (2019)
This research aims to analyze two novels of Marginal Literature: Capão Pecado (2000) and Deus Foi Almoçar (2012), both by the writer Ferréz (1975), born and raised “in the hood”, in the south zone of São Paulo. Marginal Literature, to which we refer, is produced by socially marginalized people. The novelty is that it comes as a movement from the margins, not only as a theme of fiction, but as a concrete expression of creative work and resistance, which dialogues with hegemonic instances and systems, to amplify their voices and aesthetics. The movement is of hybridization and agency tensioned between periphery and center. Based on Raymond Williams’ cultural materialism, more specific objectives emerged, such as studying other social practices associated with the writer, which allowed the understanding of Ferréz’s literature as a social production not detached from these other practices, which are immersed in the culture of the hood. Our thesis deals with what we can understand as Ferréz’s individual project, a book of his own authorship, for example, to be intimately and formally related to a collective mode. Without recognition of this collective mode (social production) it is not possible to understand the actions of the writer in the various social and cultural spheres through which he circulates. We assume that their practices take place in a counter-hegemonic sense and are potentially emerging. As a methodology, we outline feeling structures of social experiences in solution – which do not exist in evident and immediate form, since they are dispersed in everyday practices. This was possible through the analysis of the novels and of other cultural/material productions of the writer. Understanding the reality of Ferréz’s life, observing the cultural processes in which he is immersed, allowed us to access the nature of his practices and the conditions of production. By relating these issues to the literature he produces we confirmed our thesis.